Application of GIS and Earth Remote Sensing Data for the Evaluation of the Spatiotemporal Spread of Rabies in Eastern Trans-Baikal Region - I. D. Zarva; M. V. Pavlov; A. A. Sorokovoi; A. D. Botvinkin (Проблемы особо опасных инфекций, 2021)
The aim of the study was to improve monitoring of natural foci of rabies based on the use of modern technologies of cartographic analysis.Materials and methods. A retrospective study was carried out on the data of official registration of rabies in the Trans-Baikal Territory (Eastern Trans-Baikal Region) for 1950–2020. The spatial spread of rabies among animals was compared for two time periods: 1972–1978 (n=157 cases) and 2014–2020 (n=61 cases). Software packages QGIS 3.16.0, ArcMap 10.8.1, ArcScene 10.8.1 and electronic landscape-geographical maps of the world “Natural Earth”, “OpenStreetMap” were used for the mapping. Analyzed territorial units (ATUs) tied to a degree grid (0,5º × 0,5º) were marked on the cartograms. The interdependence between the localization of rabies cases and landscape elements was assessed statistically, comparing between the rabies free and the rabies affected ATUs.Results and discussion. Differences in the landscape confinedness of rabies epizootics in Eastern Trans-Baikal Region at different periods of time have been established. Until 1983, dog rabies prevailed, and epizootics spread beyond the forest-steppe zone. In 1984–2013 rabies among animals was not recorded. In 2014–2020 red foxes (Vulpes vulpes) were the main source of the rabies virus. The area of the epizootic has more than halved in comparison with 1972–1978. The main manifestations of rabies were observed at the junction of lowland and mountainous, steppe and forest areas. The rabies affected ATUs were characterized by more pronounced landscape variables. Possible routes of cross-border spread of the rabies virus have been identified. The connection between the features of the spatiotemporal spread of rabies and genetic variants of the virus, climate change, animal migrations and anthropogenic factors in Eastern Trans-Baikal Region in 1950–2020 is discussed. The results of the study are proposed to be used to adjust the programs for barrier oral vaccination of the foxes.